Perbandingan Komplikasi dan Keluaran antara Persalinan Pervaginam dan Seksio Sesaria pada Ibu dengan Riwayat Seksio Sesaria di RSD dr. Soebandi Jember - Gilang Vigorous Akbar Eka Candy; Dita Diana Parti; Rosita Dewi (Pustaka Kesehatan, 2018)
The number of cesarean section in Indonesia is 9,8% and approaching cesarean limit suggested by WHO which is 10%. The most common reason for cesarean section is prior cesarean. Cesarean section has higher maternal mortality risk compared to vaginal delivery. Vaginal delivery with prior cesarean has higher complication risk compared to cesarean section. Maternal complications and neonatal outcomes are important to decide delivery methods. Maternal complications that can be compared are postpartum infection, postpartum hemorrhage, and uterine rupture. Neonatal outcomes that can be compared are APGAR score and neonatal birth injury. This study aimed to compare maternal complications and neonatal outcomes between vaginal delivery and cesarean section in women with prior cesarean section. There was a significant difference in the incidence of postpartum infection (p=0.01) and neonatal birth injury (p=0.05). There was no significant difference in APGAR score and the incidence of postpartum hemorrhage. There was no uterine rupture observed. In conclusion, vaginal delivery is a viable option for pregnant woman with prior cesarean.